Effect of low-thermal dissection device versus conventional electrocautery in mastectomy for female-to-male transgender patients - Schlosshauer, Torsten; Kiehlmann, Marcus; Riener, Marc-Oliver; Rothenberger, Jens; Sader, Robert; Rieger, Ulrich M. (International Wound Journal, 2020)
Subcutaneous mastectomy, the first step in sexual reassignment surgery of female-to-male transsexuals, is associated with high rates of complication and revision surgery. Also, conventional electrosurgery and the associated thermal tissue damage may compromise outcome. This retrospective randomised clinical study evaluated the effect of low-thermal plasma dissection device (PEAK PlasmaBlade, Medtronic, Minneapolis, Minnesota) in comparison with conventional electrosurgery. A total of 17 female-to-male transsexuals undergoing mastectomy were randomised to PEAK PlasmaBlade on one breast side and to monopolar electrosurgery on the other side of the same patient. Wounds of 17 patients were examined histologically for acute thermal injury. Significantly less total volume of drain output (58.8 ± 37.4 mL vs 98.5 ± 76.4 mL; P =.012) was found on the PEAK PlasmaBlade side compared with the electrosurgery side. Duration of drain was significantly shorter on the PEAK PlasmaBlade side (2.5 ± 0.7 days vs 3.2 ± 0.6 days; P =.010). Furthermore, the PEAK PlasmaBlade side showed fewer thermal damages (41.2% vs 82.4%; P =.039) and thermal injury depth from PEAK PlasmaBlade side was less (3170 vs 4060 μm). PEAK PlasmaBlade appears to be superior to monopolar electrosurgery for mastectomy in female-to-male transsexuals, because it demonstrated less thermal tissue damage, less total volume of drain output, and shorter duration of drain, resulting in faster wound healing.
CRIS-Team Scopus Importer:2020-06-02
Keywords: drain output; duration of drain; electrosurgery; mastectomy; PEAK PlasmaBlade; transsexuals